Islamic Party and Pluralism: The View and Attitude of Masyumi towards Pluralism in Politics (1945-1960) - Firman Noor (Al-Jami'ah Research Centre, 2016)
This article discusses Masyumi’s response towards pluralism, particularly about the political diversity in the first fifteen years of Indonesia independent era. As the largest Islamic party in Indonesian history, Masyumi was well known by many as the champion of democracy and one of the essential elements in the nationalist movement. However, regarding pluralism, for some, Masyumi positive attitude on this matter has been doubtful, regarding this party as the guru of intolerance for some contemporary Islamic organisations. By exploring the ideals and practical aspects of this party, this article wants to show the nature of Masyumi’s view and attitude in answering political diversity that in the long run indicates the real position of this party in pluralism in politics. The discussion indicates that despite some weaknesses in undergoing the spirit of honouring diversity, in particular when dealing with the communists, Masyumi, in general, had proven its position as one of the essential elements in Indonesian political history that in many ways eager to develop and maintain the spirit of pluralism.[Tulisan ini mendiskusikan perihal respons Masyumi terhadap pluralisme, khususnya terkait dengan politik keragaman dalam rentang limabelas tahun setelah Indonesia merdeka. Sebagai partai Islam terbesar dalam sejarah Indonesia, Masyumi dikenal luas sebagai terdepan dalam praktik demokrasi dan pemain penting dalam gerakan nasionalisme. Meskipun demikian, bagi sebagian orang, respons positif Masyumi terhadap isu pluralisme tetap diragukan mengingat partai ini dianggap sebagai model intoleransi bagi organisasi Islam dewasa ini. Tulisan ini ingin menunjukkan bahwa pandangan dan sikap Masyumi dalam menjawab keragaman politik mengindikasikan posisinya yang jelas dalam pluralisme politik. Walaupun ada dukungan lemah terhadap semangat keragaman, khususnya terkait dengan kelompok komunis, secara umum Masyumi membuktikan dirinya sebagai elemen penting dalam sejarah politik Indonesia dengan berbagai cara dalam membangun dan mempertahankan semangat pluralisme. ]